Off-Site Team Retreat Practices and Teacher Job Satisfaction among Public Secondary Schools in Teso North Sub-County, Kenya - Meshack, Tumaini Albert; Achieng, Owuor Emily (European Scientific Journal, ESJ, 2026)
One strategy used by organizational leaders to encourage group thinking and produce favorable results is team building among staff members. Off-site retreats and other recreational programs run by the school administration are some of the essential practices that improve instruction and learning for the benefit of the kids. However, little research has been done on how these strategies affect teachers’ job satisfaction in various contexts, particularly in Kenya’s Teso North Sub County, which has recently seen teacher attrition and poor academic achievement. The impact of off-site retreat practices on teachers’ job satisfaction in public secondary schools in Teso North Sub County of Busia County, Kenya, was the aim of this study. The study was guided by Walberg’s Theory of Educational Productivity, which emphasizes the various factors influencing learning and academic success. Under the positivist paradigm, a descriptive survey design was used with 36 principals, 44 deputy principals, 44 senior masters, 218 class teachers, and six ward education officers as the target population. A sample size of 19 principals, 24 deputy principals, 24 senior masters, and 117 class instructors who were chosen by simple random selection was calculated using Taro Yamane’s formula. Principals and teachers were given a questionnaire, and all ward education officers were interviewed for the study. Quantitative data were analyzed using both inferential statistics (regression analysis) and descriptive statistics (mean and standard deviation). Narration was used to present the thematically analyzed qualitative data. The study found that school administrators’ off-site retreat policies had affected teachers’ job satisfaction over time (M=3.56; SD=.785). Off-site retreats were observed to cause improvements in teacher job satisfaction of 329 units (β=.329). Practices for off-site retreats should be customized to meet the unique needs and preferences of various educators.